Prevalence and Its Feto-Maternal Outcome in Placental Abruption: A Retrospective Study for 5 Years from Dubai Hospital - Shabnam Saquib; Lama Khalid Hamza; Azza AlSayed; Faiza Saeed; Masuma Abbas (Dubai Medical Journal, 2020)
Introduction: Placental abruption (PA) is a major obstetric complication leading to increased risk of maternal and neonatal morbidity and mortality globally. This study aims to determine the prevalence and its feto-maternal outcome in cases of placental abruption in our population. Methods: A retrospective descriptive case study was conducted from January 2013 till December 2017 in Dubai Hospital, Dubai, UAE. All patients admitted with suspicion of placental abruption at 28 weeks of gestation and beyond were included in the study. The clinical information like maternal age, parity, antenatal risk factors, gestational age at delivery, mode of delivery, postpartum complications and perinatal outcome were studied. Result: A total of 15,079 deliveries occurred during the study period; PA accounted for 0.61%. 62% of the women had revealed abruption and 38% had concealed abruption. The antenatal risk factors associated with abruption were diabetes (26%), chronic hypertension (2.2%), pre-eclampsia (19.5%), previous cesarean section (26%), and multiple pregnancy (9.8%). Cesarean section was the mode of delivery in 78% of abruption cases. 33% had postpartum hemorrhage and 20% had received blood products. Adverse fetal outcomes were as follows: 51% of the cases had preterm delivery, 47% of the babies had a birth weight of less than 2.5 kg, 8 cases died of intrauterine fetal death and there was 1 neonatal death. Conclusion: Even when being aware of the risk factors, placental abruption still remains unpredictable or unpreventable. Having better equipped obstetric and neonatal units with multidisciplinary management can improve both maternal and perinatal outcome in cases of placental abruption.